Teori dan Model Pengembangan Sumber Daya Manusia di Lembaga Pendidikan Islam Menurut Ahmad Fatsh Yadin - Rini Setyaningsih (Al Ulya: Jurnal Pendidikan Islam, 2021)
This study discusses the theory and model of human resource development in islamic education in Ahmad Fatah Yasin's view. The purpose of this research is to find out about the theories and models used in human resource development. This research is a Library Research (library research) using inductive analysis techniques. In the concept of human resource development Ahmad Fatah Yasin explains theories regarding human resource development, of which there are two approaches to developing the quality of Human Resources (HRM), namely the first "buy" approach, where this approach is an approach oriented to withdrawal or which is commonly referred to as Human Resources (HR) recruitment and the second "make" approach is an approach that is oriented towards the development of Human Resources in the form of: education, guidance and also training. And the most prominent thing in human resource development according to Ahmad Fatah Yasin is the human resource development model, of which there are five models in human resource development.